2010
DOI: 10.1007/s11164-010-0175-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nanoporous β-SiC fiber complex prepared by electrospinning and carbothermal reduction

Abstract: The nanoporous b-silicon carbide (SiC) nano-sized fiber complex were made from precursors of various ratios with (SiO 2 ) as silicon source and polyacrylonitrile as carbon source by simple electrospinning method and economical carbothermal reduction. The prepared samples were characterized by SEM for surface shape, XRD for crystalline properties, TGA in air for oxygen resistance, and BET for porosity according to the precursor components (C/Si mol ratio). The samples with carbon ratio to silicon (C/Si) of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…With a heat-treatment temperature of 1,000°C, an SiO 2 peak at 19.88°, characteristic of the illite, was observed without any SiC peak. At heat-treatment temperatures of 1,650 and 2,300°C, three peaks were observed, at 35.68, 60.06, and 71.80°, corresponding to the (1 1 1), (2 2 0), and (3 1 1) peaks of β-SiC, respectively; these peak positions are in good agreement with the findings of other studies [16][17][18]. β-SiC was formed as a product of the carbothermal reaction as a result of intimate contact between the SiO 2 in the illite and the phenol resin in the precursor or carbon fibers in the preform [13,15].…”
Section: Characterization Of the Prepared C/c Compositessupporting
confidence: 91%
See 1 more Smart Citation
“…With a heat-treatment temperature of 1,000°C, an SiO 2 peak at 19.88°, characteristic of the illite, was observed without any SiC peak. At heat-treatment temperatures of 1,650 and 2,300°C, three peaks were observed, at 35.68, 60.06, and 71.80°, corresponding to the (1 1 1), (2 2 0), and (3 1 1) peaks of β-SiC, respectively; these peak positions are in good agreement with the findings of other studies [16][17][18]. β-SiC was formed as a product of the carbothermal reaction as a result of intimate contact between the SiO 2 in the illite and the phenol resin in the precursor or carbon fibers in the preform [13,15].…”
Section: Characterization Of the Prepared C/c Compositessupporting
confidence: 91%
“…These peaks corresponded to α-SiC. According to a computer simulation by Pujar and Cawley [19], these peaks arise from stacking faults, which are crystallographic defects in the stacking sequence [17]. Another study reported that these peaks arise from the presence of the 2H polytype [20], which denser than those without illite (Fig.…”
Section: Effect Of the Heat-treatment Temperature On The Chemical Strmentioning
confidence: 92%
“…β-SiC support presented characteristic spectra of the two main SiC polytypes, namely α and β. Reflections at 2θ: 35.5˝[111] and 33.7˝[0001] are ascribed to hexagonal α-SiC, being the first one (C-SiC) caused by heaping defects generated during the formation of the material [36]. However, those at 2θ: 41.4˝[002], 59.9˝ [202] and 71.7˝ [113] are assigned to face-centered cubic, β-SiC [37,38]. As depicted in Figure 3, catalyst preparation procedures were confirmed to result in the formation of a pure cobalt oxide spinel phase, Co 3 O 4 , regardless of the type of precursor.…”
Section: Xrd and Temmentioning
confidence: 99%
“…For instance, carbon/silicon (C/Si) composite nanofibers can be prepared by a judicious combination of colloid electrospinning and subsequent thermal treatments. Lee et al [25] added SiO 2 nanoparticles in a PAN to fabricate SiC nano-fibres using electrospinning technique. After using many characterization tools, the SiO 2 /C ratio played a key role in controlling the fibers morphology, structure, and properties.…”
Section: Introductionmentioning
confidence: 99%